Digital Literacy Economy: Cost-Benefit Analysis of Up-skilling HR Investment in Facing Technology Operational Cost Efficiency - Parhusip, Arisma; Amril (Outline Journal of Management and Accounting, 2026)
This research investigated the economic impact of digital literacy up-skilling on operational technology cost efficiency within the service sector. The study addressed the digital paradox where high technology investments failed to yield expected productivity due to insufficient employee competency. A mixed-methods approach was utilized, incorporating Cost-Benefit Analysis and longitudinal data from fifteen companies in Medan between 2024 and 2025. Data were gathered through internal accounting reports and productivity surveys to measure the transition before and after training interventions. The analysis revealed that average digital literacy scores improved significantly from 58.4 to 82.1. Consequently, these improvements led to an 18.2% reduction in monthly maintenance costs by minimizing human errors and reducing dependency on external consultants. The calculated Human Capital Return on Investment reached 3.24, indicating that every unit of investment in digital training generated triple the value in operational savings. Statistical tests confirmed a significant negative correlation between up-skilling investment and operational waste. The study concluded that human resource development functioned as a strategic financial investment rather than a mere operational expense. These findings provided a framework for managers to integrate human resource management with accounting metrics to enhance corporate profitability in the digital era.